Candidate genes on murine chromosome 8 are associated with susceptibility to Staphylococcus aureus infection in mice and are involved with Staphylococcus aureus septicemia in humans. - Qin Yan; Sun Hee Ahn; Felix Mba Medie; Batu K Sharma-Kuinkel; Lawrence P Park; William K Scott; Hitesh Deshmukh; Ephraim L Tsalik; Derek D Cyr; Christopher W Woods; Chen-Hsin Albert Yu; Carlton Adams; et al. (PLoS ONE, 2017)
We previously showed that chromosome 8 of A/J mice was associated with susceptibility to S. aureus infection. However, the specific genes responsible for this susceptibility are unknown. Chromosome substitution strain 8 (CSS8) mice, which have chromosome 8 from A/J but an otherwise C57BL/6J genome, were used to identify the genetic determinants of susceptibility to S. aureus on chromosome 8. Quantitative trait loci (QTL) mapping of S. aureus-infected N2 backcross mice (F1 [C8A] × C57BL/6J) identified a locus 83180780-88103009 (GRCm38/mm10) on A/J chromosome 8 that was linked to S. aureus susceptibility. All genes on the QTL (n~ 102) were further analyzed by three different strategies: 1) different expression in susceptible (A/J) and resistant (C57BL/6J) mice only in response to S. aureus, 2) consistently different expression in both uninfected and infected states between the two strains, and 3) damaging non-synonymous SNPs in either strain. Eleven candidate genes from the QTL region were significantly differently expressed in patients with S. aureus infection vs healthy human subjects. Four of these 11 genes also exhibited significantly different expression in S. aureus-challenged human neutrophils: Ier2, Crif1, Cd97 and Lyl1. CD97 ligand binding was evaluated within peritoneal neutrophils from A/J and C57BL/6J. CD97 from A/J had stronger CD55 but weaker integrin α5β1 ligand binding as compared with C57BL/6J. Because CD55/CD97 binding regulates immune cell activation and cytokine production, and integrin α5β1 is a membrane receptor for fibronectin, which is also bound by S. aureus, strain-specific differences could contribute to susceptibility to S. aureus. Down-regulation of Crif1 with siRNA was associated with increased host cell apoptosis among both naïve and S. aureus-infected bone marrow-derived macrophages. Specific genes in A/J chromosome 8, including Cd97 and Crif1, may play important roles in host defense against S. aureus.